Real-time single-molecule imaging reveals a direct interaction between UvrC and UvrB on DNA tightropes - Hughes, Craig D. (Oxford University Press, 2013)
Nucleotide excision DNA repair is mechanistically conserved across all kingdoms of life. In prokaryotes, this multi-enzyme process requires six proteins: UvrA–D, DNA polymerase I and DNA ligase. To examine how UvrC locates the UvrB–DNA pre-incision complex at a site of damage, we have labeled UvrB and UvrC with different colored quantum dots and quantitatively observed their interactions with DNA tightropes under a variety of solution conditions using oblique angle fluorescence imaging. Alone, UvrC predominantly interacts statically with DNA at low salt. Surprisingly, however, UvrC and UvrB together in solution bind to form the previously unseen UvrBC complex on duplex DNA. This UvrBC complex is highly motile and engages in unbiased one-dimensional diffusion. To test whether UvrB makes direct contact with the DNA in the UvrBC–DNA complex, we investigated three UvrB mutants: Y96A, a β-hairpin deletion and D338N. These mutants affected the motile properties of the UvrBC complex, indicating that UvrB is in intimate contact with the DNA when bound to UvrC. Given the in vivo excess of UvrB and the abundance of UvrBC in our experiments, this newly identified complex is likely to be the predominant form of UvrC in the cell.